2019
DOI: 10.1111/rec.12932
|View full text |Cite
|
Sign up to set email alerts
|

Using phenological niche separation to improve management in a Northern Glaciated Plains grassland

Abstract: Many of the remaining patches of untilled (native) prairie in the Northern Glaciated Plains of North America are heavily invaded by the cool-season grasses, Bromus inermis and Poa pratensis. However, the native vegetation in these patches contains many warm-season species. This difference in phenology can be used to benefit restoration. We conducted an experiment to examine the efficacy of restoration treatments (mowing and prescribed fire) applied early in the growing season for consecutive years to decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…Our results are supported by a growing body of evidence suggesting that the timing of seeding can be a factor in determining seedling establishment success (e.g. James et al 2011, 2012; Richardson et al 2018; Bennett et al 2019). The growing season is changing for much of the Great Basin ecoregion (Tang et al 2015) and changes in precipitation timing can affect sagebrush systems (Bates et al 2006; Prevéy et al 2010), with important implications for restoration practices.…”
Section: Discussionsupporting
confidence: 85%
“…Our results are supported by a growing body of evidence suggesting that the timing of seeding can be a factor in determining seedling establishment success (e.g. James et al 2011, 2012; Richardson et al 2018; Bennett et al 2019). The growing season is changing for much of the Great Basin ecoregion (Tang et al 2015) and changes in precipitation timing can affect sagebrush systems (Bates et al 2006; Prevéy et al 2010), with important implications for restoration practices.…”
Section: Discussionsupporting
confidence: 85%
“…Although prescribed burning is typically timed to suppress invasive species by targeting the early growth period relative to the full growing season of cool-season grasses (Bennett et al, 2019;Willson & Stubbendieck, 2000), we found no collateral effects from burning on either native cool-or native warm-season grasses (Appendix S3: Table S1). These results differ from a nearby study in a mixed grass prairie in South Dakota, USA that showed that both invasive and native cool-season grasses were harmed by burning (Engle & Bultsma, 1984, but see Anderson & Bailey, 1980) for a counter example.…”
Section: Discussionmentioning
confidence: 74%
“…Phenology is an Essential Biodiversity Variable (EBV) that has been elected among the key traits to evaluate the health of the natural system worldwide (Morellato et al 2016;Kissling et al 2018). Therefore, the consideration of traits such as flowering and fruiting times associated with seed dispersal, seasonal germination strategies and pollination will certainly have positive implications for restoration practice (Viani et al 2015;Buisson et al 2017;Bennett et al 2019;Fisk et al 2019;Escobar et al 2021).…”
Section: Phenological Patterns In Restored Areas and Forest Fragmentsmentioning
confidence: 99%